An Analysis On The Use Of Grammatical Cohesive Device In Studentsâ Essay - Zulianti, Hajjah (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
This research aims to describe the grammatical cohesive devices prominently used in studentsâ essay, and to describe the studentsâ wrong used of grammatical cohesive devices in their essays. In conducting the research, the researcher uses descriptive qualitative method. The data of the research are taken from studentsâ essay on sixth semester at STKIP PGRI Bandar Lampung. The researcher uses a test to collect the data. In analyzing the data, the researcher uses the procedure such as recording the data in the data card, categorizing the data based on the four types of grammatical cohesive devices, summing up the total number of grammatical cohesive devices frequencies, finding the wrong use of grammatical cohesive device, describing the data and drawing conclusion. The result shows that the types of grammatical cohesive devices in studentsâ essay are reference, substitution, ellipsis, and conjunction. Reference and conjunction are the prominent types of cohesive devices used in studentsâ essay. The studentsâ wrongs in grammatical cohesive devices lie on the use of reference and conjunction with the total number of incorrect reference is 43 out of 515 data and incorrect conjunction is 7 out of 194 data.